EFEKTIVITAS PENDAFTARAN ONLINE TERHADAP WAKTU TUNGGU PENDONOR DARAH DI UTD PMI KOTA SURABAYA - Dhanareswari, Putu Ayu; Amalia, Yustisia; Widuri, Sasi; Badrus, Arkha Rosyaria; Khairoh, Miftahul (Jurnal Medicare, 2025)
UTD PMI Surabaya City has provided online registration services, donors can register at home, because online donor registration can be accessed through the application provided by UTD PMI Surabaya City. The standard service time engaged in hospital health services regarding outpatient care is ≤ 60 minutes. This study is a quantitative study with a pre-experimental design using a one group pretest-posttest approach. This study aims to determine the effectiveness of Online Registration on Blood Donor Waiting Time at UTD PMI Surabaya City. Based on the results of the Mann Whitney test using SPSS in the study of the Effectiveness of Online Registration on Blood Donor Waiting Time at UTD PMI Surabaya City, the Sign value (2-tailed) = 0.000 is where the value is smaller than the significance value <0.05 so that Ho is rejected and Ha is accepted, which means there is effectiveness of Online Registration on Blood Donor Waiting Time at UTD PMI Surabaya City.